MULTIMODAL IMAGING OF GEOGRAPHIC AREAS OF RETINAL DARKENING. Issue Volume 9:Issues 4(2015:Autumn) (2015) - Moysidis, Stavros N.; Koulisis, Nicole; Ameri, Hossein; Matsunaga, Douglas; Yi, Jack; Isozaki, Veronica L.; Kashani, Amir H.; Olmos de Koo, Lisa C.
Abstract : Purpose: To describe the clinical and multimodal imaging characteristics of a patient with unilateral asymptomatic dark retinal lesions corresponding to ellipsoid zone hyporeflectivity on optical coherence tomography (OCT). Methods: The authors report a case of a 35-year-old man with HIV who presents with asymptomatic dark geographic retinal lesions corresponding to ellipsoid zone hyporeflectivity on OCT. Multimodal imaging techniques, including fundus color and widefield photographs, autofluorescence, spectral domain OCT (Spectralis, Heidelberg, Germany), prototype spectral domain OCT (Carl Zeiss Meditec, Dublin, CA) with OCT angiography, and en face images, were performed to evaluate and characterize the morphology of these lesions. Results: Clinical examination and multimodal imaging reveal geographic darkening of the retina. Optical coherence tomography conveys hyporeflectivity of the ellipsoid zone band, which occurs abruptly and is present only in the areas of geographic retinal darkening. Optical coherence tomographic angiography shows a qualitatively similar appearance of the vasculature from the superficial retina through the avascular retina and the choriocapillaris, on both sides of the demarcation of retinal darkening, and also as compared to the unaffected eye. En face images from spectral domain OCT reveal an abrupt darkening of the tissue that localizes and is limited to the ellipsoid zone, with similar topographic appearance across the demarcation line. Conclusion: Geographic areas of darkening with photoreceptor hyporeflectivity have been described previously as "dark without pressure." In this case, the authors demonstrate photoreceptor hyporeflectivity that localizes to the clinically darkened areas, without topographic qualitative differences on en face spectral domain OCT images. The authors term these dark areas as geographic areas of retinal darkening because of ellipsoid nonreflectivity (GARDEN) spots. Abstract : Case of asymptomatic dark geographic retinal lesions corresponding to ellipsoid zone hyporeflectivity on optical coherence tomography. Optical coherence tomographic angiography reveals qualitatively similar appearance of the vasculature at the areas of retinal darkening compared to the adjacent normal-appearing retina, with en face imaging revealing darkening of the tissue limited to the ellipsoid zone.